Should healthcare professionals include aspects of environmental sustainability in clinical decision-making?: a systematic review of reasons - Kuiter, Sarah Gabriela; Herrmann, Alina; Mertz, Marcel; Quitmann, Claudia; Salloch, Sabine (BMC medical ethics, 2025)
Background Healthcare systems worldwide are large emitters of greenhouse gases and contribute to the worsening climate crisis. Attempts to reduce emissions are already being made at various levels of the healthcare system. However, the extent to which considerations of environmental sustainability should be incorporated into clinical decision-making at the individual level is unclear. - Methods We conducted a systematic review of the reasons stated for and against including aspects of environmental sustainability in the clinical decision-making of healthcare professionals. PubMed was searched as the primary data source. We screened title and abstract of all publications and performed a citation tracking of the included publications in Web of Science. All publications identified were screened for references. We performed a qualitative data analysis with a deductive-inductive approach according to Kuckartz. We used RESERVE as a reporting guideline. - Results Twenty-three publications were qualitatively analyzed in full-text. To cluster the reasons we used the four deductive categories of autonomy, beneficence, non-maleficence and justice according to the principles of biomedical ethics by Beauchamp and Childress. Additionally, the following inductive categories have emerged: autonomy transformed, non-maleficence transformed, environmental justice, professionalism, politicization, reasons addressing levels of action and an ‘other’ category. The review showed that the debate is still in its infancy and shaped by perspectives from high-income countries, while the perspective of low- and middle-income countries is lacking. For some deductively categorized reasons, a transformation towards a less individual-oriented perspective was often observed. However, it is important to recognize that the individual level is intertwined with the systemic level in the context of climate change mitigation. - Conclusion This systematic review of reasons draws attention to a possible transformation of bioethical principles, which has not yet found favor in many guidelines or codes of professional associations. It is also intended to serve as Should healthcare professionals include